There's a boy in the girls' bathroom - Sachar, Louis, 1954-; Bloomsbury Publishing (London : Bloomsbury, 2007)
An unmanageable, but lovable, eleven-year-old misfit learns to believe in himself when he gets to know the new school counselor, who is a sort of misfit too.
5.0
3-6
Keywords: Friendship -- Juvenile fiction; Human behavior -- Juvenile fiction; Student counselors -- Juvenile fiction; Behavior -- Fiction; Counselors -- Fiction; Friendship -- Fiction; Schools -- Fiction; Human behavior -- Fiction; School stories